The Impact of an Educational Video on Clinical Trial Enrollment and Knowledge in Ethnic Minorities: A Randomized Control Trial - Skinner, Jeannine S.; Fair, Alecia M.; Holman, Alexis S.; Boyer, Alaina P.; Wilkins, Consuelo H. (Frontiers in Public Health, 2019)
Introduction: Innovative methods to increase awareness about clinical trials and address barriers associated with low participation among racial/ethnic minorities are desperately needed. African Americans comprise 5% of all clinical trial participants, and Hispanics make up 1%. Use of multimedia educational material has shown promise as an effective strategy to increase minority clinical trial enrollment. However, this approach has not been broadly implemented. We tested the effect of a video educational program on clinical trial knowledge and enrollment in a sample of oncology outpatients. Methods: A randomized controlled trial was conducted with 63 oncology patients without previous history of clinical trial participation. Participants were randomly assigned to the intervention, to watch a clinical trial educational video in the office, or to the control group which did not receive in-office education. The Clinical Trial Knowledge survey was administered before the intervention and 1 week after the intervention. Participation in clinical trials was assessed 1-year post study participation. Results for white participants and ethnic minorities were compared. Ethnicity was self-reported through the electronic health record and confirmed by self-reporting on questionnaire. Results: Sixty-three participants were recruited in this study. At 1-year follow-up, 3 participants enrolled in clinical trials in the study group which had received office-based video intervention and 2 participants enrolled in the control group (Z = 0.39, p = 0.69). These results were not statistically significant. Impact of the intervention by ethnicity could not be assessed due to low total clinical trial enrollment. The video intervention did not change knowledge, attitudes, or barriers as measured by the Clinical Trial Knowledge Survey. Minority participants did report significantly more negative beliefs and barriers to participation than white participants. Conclusions: Increasing awareness and knowledge about clinical trials in underrepresented communities is an important step to providing opportunities for participation. Future studies should focus on how to address the negative expectations of clinical trials and the greater information needs in minority populations. Tailored or personalized messaging may address negative perceptions of clinical trial participation.